Ceramics Designing Applied Derive from Local Wisdom of Bankruat District, Buriram Province. - คำมณี อภิชาติธำรง (Journal of Fine and Applied Arts Khon Kaen University, 2018)
The present investigation was undertaken with the following objectives:To study the development of the ceramics motifs, viz., pattern, form including its producing process. To apply the ancient BanKruat ceramics in order to create innovated ceramics design. The research was carried out by treatise review, field observation and interviewing/inquiring a group of nine local connoisseurs-cum-practitioners and the others involved throughout the field study area. Therefore this present work as if it was a start-up to maintain the ancient production characteristics and enabled to revive the craftsmanship in order to develop the creative products and to succeed the cultural inheritance.